IMPLEMENTASI PROGRAM PEMBERIAN OBAT PENCEGAHAN MASSAL (POPM) KAKI GAJAH (FILARIASIS) DI KECAMATAN BANGKO PUSAKO KABUPATEN ROKAN HILIR - Ramiza Safitri; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Health in social life is a prosperous state of body, soul, and social that allows every person to live socially and economically productive, where the position of health is very important in improving the life of society. The prevention and elimination of elephantiasis is now a concern of the Government and is one of the disease control programs that should be pursued in a more systematic and sustainable manner. Filariasis or better known also elephantiasis disease is a chronic infectious disease that is always present in the tropics caused by filaria worm infection. The Filariasis Prevention Bulk Drug Program (POPM) is an action that prioritizes people's safety above individual interests. The purpose of this research is to see how the implementation of the program of drug prevention of bulk (POPM) of elephantiasis (filariasis) in Pangko pusako district of Rokan Hilir district. The concept of theory used is, the implementation proposed by Edward III which says that there are four variables that determine the successful implementation of a policy, namely: Communications, Resources, Disposition and Bureaucratic Structure. This research uses qualitative method with descriptive data. In collecting data of researcher use purposive sampling method as source of information and data analysis with triangulation technique. The results showed that the implementation of the program of prevention of bulk foot (elephant) foot mass (filariasis) in Bangko Pusako district of Rokan Hilir district has been running well, but only the lack of comprehensive socialization or counseling in the implementation. In addition, the community should also be the target group of the program has awareness to take the drug, so that the program can be done as expected.Keywords : Implementation, medicine, Filariasis